Management of Islamic Religious Education Learning Based on Cooperative Problem E-Learning During The Covid-19 Pandemic (Study on Muhammadiyah High School Sukoharjo, Central Java) - Supriyanto Supriyanto; Amrin Amrin (Jurnal Pendidikan dan Konseling (JPDK), 2022)
This study aims to determine how to manage Islamic Religious Education learning by using cooperative problem e-learning during the Cocid 19 Pandemic. This type of research uses a qualitative type with field studies on Muhammadiyah High School Sukoharjo, Central Java with a descriptive analysis approach.The results showed that shows that the method cooperative problems e-learning is the ideal solution in dealing with the COVID-19 pandemic in Islamic Religious Education learning. Because this method can connect and solve problems that occur between students and technology today. The collaboration of the two concepts of cooperative learning and e-learning problems makes a very significant contribution to students to have the ability to understand the material, communication skills and interpersonal skills, problem solving skills, critical analysis and skills in increasing faith, piety, and noble character, religious tolerance and harmony, and other skills needed by students. Thus, with the presence of technology 4.0, it really provides convenience in the limitations of the learning process through concepts and methods that can be solved easily cooperative problems e-learning